Desertification risk assessment and management program - M. Akbari; M. Ownegh; H.R. Asgari; A. Sadoddin; H. Khosravi (Global Journal of Environmental Science and Management)
Risk assessment provides the possibility of planning and management to prevent and reduce the risk of desertification. The present study is aimed to assess the hazard and risk of desertification and to develop management programs in the semi-arid western regions of Golestan Province in Iran. Desertification rate was obtained using the Iranian model of desertification potential assessment. Since the rating system was considered for the indicators, data analyses were carried out according to the Mann-Whitney test. The risk of desertification was calculated based on hazard, elements at risk and vulnerability assessment maps. The intensity of desertification was estimated to be medium. Among the factors affecting desertification, agriculture by the weighted average of 3.22 had the highest effect, followed by soil, vegetation, water and wind erosion criteria by weighted averages of 2.45, 2.32, 2.15 and 1.6 respectively. Desertification risk assessment results also showed that about 78% of central and northern parts of the region, with the largest population and residential centers, surface and underground water resources, agriculture and horticulture, is confronted with a high to very high degree of risk. Management plans and control measures, based on risk values were presented in four activities (with two management priorities under critical and non-critical conditions). For the management program with the largest area. Control measures and strategies such as the establishment of halophytic and xerophytic plants, drainage networks, resilient facilities and infrastructure were proposed. Reducing the risk of desertification, could play a crucial role in the sustainable development of drylands and desert ecosystems.